DEVELOPMENT OF STUDENT WORKSHEETS BASED ON THE CONTEXTUAL TEACHING AND LEARNING APPROACH ON QUADRILATERALS AND TRIANGLES IN CLASS VII MIDDLE SCHOOL - Yuderlina Waruwu (Afore : Jurnal Pendidikan Matematika, 2023)
The purpose of this study is to develop Contextual Teaching Learning-based Student Worksheets on quadrilaterals and triangles that are valid, practical and effective. The type of research used in this research and development or (R&D) with the ADDIE Model (Analysis, Design, Development, Implementation, Evaluation). Data collection techniques used are validation sheets, student response questionnaires, and student learning outcomes tests. While the data analysis technique used is qualitative and quantitative data analysis. Based on the research and discussion, the validation results from material experts were 89.33% with very feasible criteria, the validation results from media experts were 88% with very feasible criteria, and the validation results from linguists were 84.44% with satisfactory criteria. The results of the practicality test from individual trial respondents were 81.25% with interesting and practical criteria, the results of small group trial respondents were 87.5% with very interesting and very practical categories, and the results of field trial respondents were 94.11% with categories are very interesting and very practical. The effectiveness results obtained an average value of 96% with a very high category. Researchers hope that this LKPD can make it easier for students to understand the concept of quadrilaterals and triangles.